Investigation of rainwater infiltration with emphasis on hydro-geological as well as hydrological conditions - Zeleňáková, Martina; Hudáková, Gabriela; Tometz, Ladislav; Hlavatá, Helena (International Conference “Environmental Engineering”, 2017)
Urban drainage has become one of the most important aspects of urban development. Ensuring long erm functioning of sewer systems and wastewater treatment plants is associated with constantly rising costs, and it is clear nowadays that the contemporary method of urban drainage cannot possibly be implemented worldwide because of the financial burden. The existing method of urban drainage continues to threaten the status of water flow and water sources. Urban hydrology has evolved to improve the way urban run ff is managed for flood protection, public health and environmental protection. The essence of the future solution resides in finding an acceptable compromise or an alternative solution for rainwater drainage from urban areas. The content of this paper is research focused on the infiltration of water from surface runoff and comparison of ground testing, laboratory analysis and numerical analysis of filtration coefficient. The foundation for improving the effectiveness of urban drainage will be created through the proposal and comparison of infiltration conditions. The topic of the paper emerged because of insufficient information about infiltration systems in the Slovak technical regulations and the lack of support for water infiltration from surface runoff. This paper points out the fundamentals, principles and development of proposals for infiltration facilities. The aim of the paper was to expand the body of scientific knowledge in research and solutions for infiltration of water from surface run-off with emphasis on the infiltration capacity of the selected area and intensity of precipitation.